Dynamics of the pedestal in the recovery phase between type-III ELMs. (5th February 2018) - Kong, D.F.; Lan, T.; Liu, A.D.; Yu, C.X.; Zhao, H.L.; Shen, H.G.; Yan, L. W.; Dong, J. Q.; Xu, M.; Zhao, K. J.; Cheng, J.; Duan, X. R.; et al.
Abstract: Dynamics of the pedestal between type-III ELMs have been studied by a particular designed four-step probe array on HL-2A tokamak. The recovery of the edge transport barrier (ETB) can be divided clearly into three different phases. Inconsistent with the dynamics during the type I ELMy discharge, our results on HL-2A show that the (electron) temperature pedestal is recovered first, well before the ELM crash, while the density and pressure pedestals are still evolving slowly until the next ELM. The fast recovery of the temperature pedestal can trigger a low-frequency electrostatic coherent mode (LFM) (20–120 kHz) in the edge plasma. Direct and indirect measurements reveal that the LFM can drive strong inward particle flux. After the excitation, the LFM can slow down the further recovery of the temperature pedestal. Yet, the excitation of the LFM may help the recovery of the density pedestal. The structure and excitation studies indicate that the LFM may be the ion temperature gradient driving mode (ITG) excited in the edge plasma and plays a critical role in the recovery of pedestal between type-III ELMs.